Development of a Stock Rebound Prediction Model on the LQ45 Index Using Relative Strength Index (RSI), Moving Average (MA), and Ichimoku Kinko Hyo Analysis - Agung Diva Bramantya, I Gusti Ngurah; Oktaryani, Sri; Anwar, Adrianda (Ikatan Da'i Indonesia, 2026)
This research aims to analyze the effectiveness of technical indicators, namely Relative Strength Index (RSI), Moving Average (MA), and Ichimoku Kinko Hyo, in predicting stock rebound patterns in the Indonesian stock market between November 2024 and September 2025. The study investigates how these indicators react to sharp price declines and the potential for price recovery. Using historical data from selected stocks listed in the LQ45 index, this research examines the occurrence of oversold conditions, signal accuracy, and trend reversals. The results show that RSI effectively signals potential rebound opportunities when the stock reaches oversold levels, although false signals occur during periods of market inefficiency. While MA provided useful trend analysis through crossing signals, the resulting price movements often lacked the sustainability of a full recovery. Similarly, Ichimoku Kinko Hyo, despite indicating strong support levels and potential bullish trends, also failed to predict consistent price rebounds, especially during sideways market conditions. This study contributes to the understanding of how technical indicators perform in volatile market conditions, highlighting both their strengths and limitations. The findings suggest that while these indicators can provide valuable insights into price movements, relying solely on them without considering broader market factors may lead to inaccurate predictions. The research recommends combining multiple technical indicators with other forms of analysis, such as fundamental analysis and market sentiment, to improve investment decision-making processes. The study's implications are relevant for investors, offering insights into the use of technical analysis in times of market uncertainty and the importance of recognizing the contextual limitations of technical indicators in predicting stock price recovery .